Effect of Coconut Shell Powder and MgO-SiO₂ Composite as Flux on Fume Emission, Strength, Hardness, and Microstructure in SMAW Welds : A review - Monica, Zelvia; Nurato, Nurato (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2025)
Shielded Metal Arc Welding (SMAW) is extensively applied across industries due to its simplicity and versatility. However, conventional flux materials commonly used in SMAW produce toxic fumes that pose environmental and health hazards. This review investigates the potential of coconut shell powder, combined with magnesium oxide (MgO) and silicon dioxide (SiO₂), as a sustainable flux alternative. Coconut shell powder, a carbon-rich agricultural waste, has demonstrated effectiveness in reducing fume emissions, while MgO and SiO₂ enhance slag formation, arc stability, and weld metallurgical quality.Replacing conventional flux with up to 30% coconut shell powder has been shown to reduce fume emissions by approximately 40%. The addition of MgO-SiO₂ composites improves weld tensile strength and hardness. Microstructural observations reveal finer grain structures, reduced porosity, and the formation of acicular ferrite, which contributes to increased toughness and crack resistance. This study aims to address gaps in previous research, which often focused on non-welding applications or did not assess key welding characteristics such as fume generation, mechanical properties, and microstructure. By integrating biomass waste and ceramic compounds, the proposed flux formulation offers an eco-friendly and cost-effective alternative for SMAW electrodes.In addition to enhancing weld quality, this approach supports environmental sustainability by utilizing locally abundant, underused natural resources. It also reduces dependence on synthetic flux minerals, making it suitable for widespread use in tropical regions. Further research is recommended to optimize the composition and evaluate performance across various base metals and welding conditions.